The Role of Surveillance Inspections in Reducing False-Positives of SARS-CoV-2 Omicron Variants during the COVID-19 Epidemic - Li-Li Liu; Yu-Hong Zheng; You-Quan Zhang; Jin-Piao Lin; Zhi-Lin Luo; Liu-Min Yu; Shi-Hua Gao; Falin Chen (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objective. This study aims to assess the effectiveness of surveillance inspections conducted by the provincial health committee in Quanzhou city during a COVID-19 outbreak in reducing false-positive results in SARS-CoV-2 RT-PCR assays. Method. The team conducted on-site inspections of laboratories that participated in mass screening, recording any violations of rules. Results. The positive cases in five rounds of mass screening were 23, 173, and 4 in Licheng District, Fengze District, and Luojang District, respectively. The false-positive rates in the five rounds of mass screening were 0.0099%, 0.0063%, 0.0018%, 0.0006%, and 0%, respectively. The study also recorded that the number of violations in the seven selected laboratories was 36, 68, 69, 42, 60, 54 and 47. The corresponding false-positive rates were 0.0012%, 0.0060%, 0.0082%, 0.0032%, 0.0060%, 0.0027%, and 0.0021%, respectively. The study found a positive correlation between false-positive rates and the number of violations (r = 0.905, P=0.005), and an inverse correlation between false-positive rates and the frequency of surveillance inspections (r = −0.950, P<0.001). Conclusion. Daily surveillance inspection in laboratories can remind laboratories to strictly comply with standard procedures, focus on laboratory quality control, and reduce the occurrence of false-positive cases in SARS-CoV-2 nucleic acid tests to some extent. This study recommends that government decision-making departments establish policies and arrange experts to conduct daily surveillance inspections to improve laboratory quality control.